Silver(I) Ion Removal Efficiency of Activated Carbon Prepared from Terminalia-bellerica (Barro) Seed Stone - Adhikari, Mandira Pradhananga; Lamsal, Sandeep Sharma (Journal of Nepal Chemical Society, 2021)
Phosphoric acid-activated Terminalia-bellerica (Barro) seed stone powder was carbonized in a muffle furnace at three different temperatures (300, 400, and 500oC). The activated carbons (BAC-300, BAC-400, and BAC-500) were characterized by using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), methylene blue number, and iodine number. The iodine number (357 mg/g) and specific surface area (537 m2/g) were a maximum for BAC-400. The BACs followed Langmuir adsorption isotherm and the maximum methylene blue adsorption capacity was 212.77 mg/g. The silver ion removal efficiency was a maximum at pH 6, 3 mg/L of adsorbent dose, and 20 mg/L of silver ion concentration. The BAC-400 could adsorb 40 % of silver ion within 5 mins with the initial Ag(I) ion concentration of 20 mg/L and an adsorbent dose of 1 mg/L. The percentage of adsorption enhanced to 100% with the increment of adsorbent doseto3 g/L.The adsorption kinetics of silver (I) ion on BAC-400 was well fitted to pseudo-second-order kinetics suggesting the chemisorption of silver ions. All the results attributed that low-cost viable adsorbent can be prepared from Barro seed stone for the efficient removal of silver ion from aqueous solution.